2019
DOI: 10.25083/rbl/24.2/324.331
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic alleles of gammaCop gene from Drosophila melanogaster display an unexpected expression pattern in mutant eggs, testes and embryos

Abstract: We report an unusual overexpression pattern of the hypomorphic alleles γCop 11a , γCop 14a and γCop 16b of gammaCop gene from Drosophila melanogaster. Each allele contains a distinct short remnant of the P{lacW} transposon located in 5'UTR. Repeated crosses between γCop 14a /γCop 14a females and γCop 11a /γCop 11a or γCop 16b /γCop 16b males proved to be sterile, but the reciprocal ones are fertile.The most severe allele is γCop 14a since a γCop 14a /γCop 14a line cannot be obtained. Remarkably, qRT-PCR perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…The insertion determines a recessive lethal allele as revealed by obtaining precise viable excisions of P{lacW} S 057302 —proof that there is no other hidden mutation in the l(3)S057302 chromosome accountable for the lethal phenotype [ 28 ]. Moreover, we found that γCOP S057302 fails to complement the lethality of γCOP ∆114 (located in a chromosome 3 with a different mutational background than l(3)S057302 ), confirming data of Jayaram et al [ 29 ] and the fact that γCOP is indeed an essential gene, being also involved in fruit flies’ fertility [ 30 ]. The crosses among γCOP 14a /γCOP 14a males and females are always sterile, but both homozygous males and females are fertile when crossed with flies having at least one wild-type (WT) copy of γCOP ( γCOP WT ).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The insertion determines a recessive lethal allele as revealed by obtaining precise viable excisions of P{lacW} S 057302 —proof that there is no other hidden mutation in the l(3)S057302 chromosome accountable for the lethal phenotype [ 28 ]. Moreover, we found that γCOP S057302 fails to complement the lethality of γCOP ∆114 (located in a chromosome 3 with a different mutational background than l(3)S057302 ), confirming data of Jayaram et al [ 29 ] and the fact that γCOP is indeed an essential gene, being also involved in fruit flies’ fertility [ 30 ]. The crosses among γCOP 14a /γCOP 14a males and females are always sterile, but both homozygous males and females are fertile when crossed with flies having at least one wild-type (WT) copy of γCOP ( γCOP WT ).…”
Section: Discussionsupporting
confidence: 87%
“…The data fit the same hierarchy of the allelic severity scale that we previously reported for lethality and sterility of these γCop alleles [ 30 ]. Therefore, the phenotypic severity modulation of lethality, sterility, and commensal microbiota load are reasonably accountable for the differences between the two alleles of γCOP .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations